PENYELESAIAN SENGKETA PASAR MODAL MELALUI NEGOSIASI - Muhammad Nurhadi; Abdul Mujib; Adet Tamula Anugrah (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2023)
The role of the capital market for development is very important. But on the other hand, potential legal problems are inevitable. Disputes become potential cases of lawlessness in the capital market. Therefore, the focus of this study is to examine the settlement of capital market disputes through negotiations. This research uses the library research method with a content analysis approach. Data collection is obtained from books and journals. Data analysis is carried out through the stages of data reduction, data presentation, and data verification. The results of this study show that negotiation is an alternative to resolving dispute cases carried out by parties to disputes by discussing settlements without the involvement of third parties. The advantages of capital market dispute resolution are that it is not costly, is informal, prevents hostilities, and has a quick resolution time.